Novel organic salts based on quinoline derivatives: The in vitro activity trigger apoptosis inhibiting autophagy in Leishmania spp. (25th September 2018) - Calixto, Stephane Lima; Glanzmann, Nícolas; Xavier Silveira, Michele Maria; da Trindade Granato, Juliana; Gorza Scopel, Kezia Katiani; Torres de Aguiar, Thiago; DaMatta, Renato Augusto; Macedo, Gilson Costa; da Silva, Adilson David; Coimbra, Elaine Soares
Abstract: Leishmaniases are infectious diseases, caused by protozoa of the Leishmania genus. These drugs present high toxicity, long-term administration, many adverse effects and are expensive, besides the identification of resistant parasites. In this work, the antileishmanial activity of quinoline derivative salts (QDS ) was evaluated, as well as the toxicity on mammalian cells and the mechanism of action of the most promising compound. Among the compound tested, only the compoundQDS3 showed activity against promastigotes and amastigotes of Leishmania spp., being more active against the intracellular amastigotes of L. amazonensis -GFP (IC50 of 5.48 μM). This value is very close to the one observed for miltefosine (IC50 of 4.05 μM), used as control drug. Furthermore, the compoundQDS3 exhibited a selective effect, being 40.35 times more toxic to the amastigote form than to the host cell. Additionally, promastigotes of L. amazonensis treated with this compound exhibited characteristics of cells in the process of apoptosis such as mitochondrial membrane depolarization, mitochondrial swelling, increase of ROS production, phosphatidylserine externalization, reduced and rounded shape, and cell cycle alteration. The integrity of the plasma membrane remained unaltered, excluding necrosis in treated promastigotes. The compoundQDS3 inhibited the formation of autophagic vacuoles, which may have contributed to parasite death by preventing autophagic mechanisms in the removal of damaged organelles, intensifying the damage caused by the treatment, highlighting the antileishmanial effect of this compound. In addition, treatment withQDS3 induced increased ROS levels in L. amazonensis -infected macrophages, but not in uninfected host cell. These data reinforce that the induction of oxidative stress is one of the main toxic effects caused by the treatment with the compoundQDS3 in L. amazonensis, causing irreversible damage and triggering a selective death of intracellular parasites. Data shown here confirm the biological activity of quinoline derivatives and encourage future in vivo studies with this compound in the murine model. Highlights: Organic salts were screened as potential antileishmanial agents. The quinoline derivative salt (QDS3 ) exhibited the best antileishmanial effect. QDS3 induced apoptosis in promastigotes of L. amazonensis. This compound inhibited the formation of autophagic vacuoles. The oxidative stress can be the key event in the induction of apoptosis.